PENINGKATAN KOMPETENSI GURU MELALUI MANAJEMEN PEMBELAJARAN KREATIF DI SD NEGERI 1 MAGELANG KECAMATAN KALIWUNGU KABUPATEN KENDAL - Kristanto Kristanto (Universitas PGRI Semarang, 2011)
Teacher Competency Development througt Creative Learning Management at SD Negeri 1 Magelung Kecamatan Kaliwungu Kabupaten Kendal SD Negeri 1 Magelung is an SD on level. The excellent achievement derives from the management and the teacher who have competency in their subject.In this research, researcher described in the implementation of creative learning management applied on this SD. Besides tat, the researcher also analyzed the role of implementing creative learning management in developing teacher competency. The method of the research was descriptive qualitative. The subject of the research were all teachers of the SD Negeri 1 Magelung Kendal. As for the data for the collection, the researcher used documentative method, interview and observation. And for the technique of analisys, the researcher used model of data reducsion, data display and concluding drawing. Whereas for the data validation technique, the researcherused triangulation technique, member check, dependability and confirmability. The result of the research showed that the creative learning management could be understood as a maximaze student achievement. The creative learning management could be understood as a process of choosing and implementing strategy. Strategy is a pattern of human resource allocation wich enables organizations to mountain their work. The implementation of the creative learning management was done profesissionally and proportionally. Each teacher was required to have capacity and to be able to develop the learning method. In general, the creative learning management was proven to be able to help the teachers to develop the ability of teacher competence I teaching. Based on the research result, it can be advised that teacher?óÔé¼Ôäós role and duty is one of determinant factor for the success of education. So, existence and development of teaching profession becomes an essential discourse for the government. Deterioration of education is not caused by curriculum but by lac teacher?óÔé¼Ôäós professionalism and student?óÔé¼Ôäós reluctant in learning. The professionalism focuses on knowledge mastery or management capability and implementation strategy. Kata Kunci: Competency, Learning Management, Creative Learning